PENGARUH PEMEDIASIAN BUDAYA ORGANISASI TERHADAP KINERJA (Fokus Ekonomi, 2010)
Within this study, we use path analysis to explore the influence of structure, strategy, and career system on corporate culture and the influence of corporate culture on organizational performance. A questionnaire survey is utilized to focus on manufacturing industries and service industries for empirical study. A total of 270 questionnaires were sent with 98 valid questionnaires received. Among them, 45 replies were from service industries and 53 replies were from manufacture industries. Based on the study results, we make four conclusions: 1) strategy have a positively significant influence on corporate culture; 2) stucture have a positively significant influence on corporate culture; 3) career system have a positively significant influence on corporate culture; 4) career system have a positively significant influence on organizational performance.